The way things work now : from levers to lasers, windmills to Wi-Fi, a visual guide to the world of machines - Macaulay, David; Ardley, Neil (Houghton Mifflin Harcourt, 2016)
Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines.